1982
DOI: 10.1111/j.1469-185x.1982.tb00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Avian Egg Shells and Their Adaptive Value

Abstract: Summary I. An arbitrary classification of avian eggshells is proposed. 2. The role of the eggshell in conserving the water in eggs at oviposition is discussed. There is as yet no correlation between this property and the pore systems in avian eggshells. 3. The pore systems may act as diffusion pathways and the hypothesis has been advanced that in many eggs the shells are adapted so that restriction of gaseous diffusion by mud, preening oils and nest debris is prevented. 4. The mechanical properties of the shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 61 publications
2
90
1
2
Order By: Relevance
“…Here we showed that the surface topography of brush-turkey eggs, determined by the presence of nanoscale spheres composed of calcium phosphate, renders the eggs hydrophobic, decreases bacterial attachment and is most likely the major component preventing trans-shell penetration. Elemental analysis showed high concentrations of phosphorus on the layer of spheres of the brush-turkey cuticle, which likely corresponds to the presence of calcium phosphate (Board, 1982). A cuticle composed of calcium phosphate is rare compared with the more common calcium carbonate (vaterite) or the most ubiquitous organic cuticle (glycoprotein), and has only been found in eggshell cuticles of greater flamingos and guinea fowl (Tullett et al, 1976), grebes (Board et al, 1984) and Mallee fowl .…”
Section: Discussionmentioning
confidence: 99%
“…Here we showed that the surface topography of brush-turkey eggs, determined by the presence of nanoscale spheres composed of calcium phosphate, renders the eggs hydrophobic, decreases bacterial attachment and is most likely the major component preventing trans-shell penetration. Elemental analysis showed high concentrations of phosphorus on the layer of spheres of the brush-turkey cuticle, which likely corresponds to the presence of calcium phosphate (Board, 1982). A cuticle composed of calcium phosphate is rare compared with the more common calcium carbonate (vaterite) or the most ubiquitous organic cuticle (glycoprotein), and has only been found in eggshell cuticles of greater flamingos and guinea fowl (Tullett et al, 1976), grebes (Board et al, 1984) and Mallee fowl .…”
Section: Discussionmentioning
confidence: 99%
“…Eggs of species that nest in more humid and wet environments are more likely to have cuticular nanospheres. This is most likely because humid environments increase the risk of flooding of eggs and/or microbial infection [10,21]. Therefore, these data suggest that nanospheres are selected for protection against occlusion of pores and microbial or other environmental threats.…”
Section: Discussionmentioning
confidence: 96%
“…In wet environments, the eggshell pore canal can become flooded and impede exchange of vital gasses through the shell, impairing embryonic growth and potentially leading to asphyxiation [21]. In addition, bacterial transport with liquid water or water vapour through the pores is a mechanism for microbial infection [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cuticle is an uneven layer whose inner part is made up of a protein-carbohydrate complex containing a small amount of the crystal complex hydroxyapatite deposited during the final phase of eggshell calcification; the outermost layer remains non-mineralized (Rose-Martel et al, 2012). Its function is either to bridge the outer pore openings or to extend down into the pore canals, plugging them (Board, 1982). The cuticle also links the lumina of pore canals to the egg's exterior and, thereby, serves as a pathway for gas diffusion (Board and Scott, 1980).…”
Section: The Eggshell and Cuticlementioning
confidence: 99%